Costs and cost effectiveness of different strategies for chlamydia screening and partner notification: an economic and mathematical modelling study. (4th January 2011) - Turner, Katy; Adams, Elisabeth; Grant, Arabella; Macleod, John; Bell, Gill; Clarke, Jan; Horner, Paddy
Abstract : Objectives To compare the cost, cost effectiveness, and sex equity of different intervention strategies within the English National Chlamydia Screening Programme. To develop a tool for calculating cost effectiveness of chlamydia control programmes at a local, national, or international level. Design An economic and mathematical modelling study with cost effectiveness analysis. Costs were restricted to those of screening and partner notification from the perspective of the NHS and excluded patient costs, the costs of reinfection, and costs of complications arising from initial infection. Setting England. Population Individuals eligible for the National Chlamydia Screening Programme. Main outcome measures Cost effectiveness of National Chlamydia Screening Programme in 2008–9 (as cost per individual tested, cost per positive diagnosis, total cost of screening, number screened, number infected, sex ratio of those tested and treated). Comparison of baseline programme with two different interventions—(i) increased coverage of primary screening in men and (ii) increased efficacy of partner notification. Results In 2008–9 screening was estimated to cost about £46.3m in total and £506 per infection treated. Provision for partner notification within the screening programme cost between £9 and £27 per index case, excluding treatment and testing. The model results suggest that increasing male screening coverage from 8% (baseline value) to 24% (to match female coverage) would cost an extra £22.9m and increase the cost per infection treated to £528. In contrast, increasing partner notification efficacy from 0.4 (baseline value) to 0.8 partners per index case would cost an extra £3.3m and would reduce the cost per infection diagnosed to £449. Increasing screening coverage to 24% in men would cost over six times as much as increasing partner notification to 0.8 but only treat twice as many additional infections. Conclusions In the English National Chlamydia Screening Programme increasing the effectiveness of partner notification is likely to cost less than increasing male coverage but also improve the ratio of women to men diagnosed. Further evaluation of the cost effectiveness of partner notification and screening is urgently needed. The spreadsheet tool developed in this study can be easily modified for use in other settings to evaluate chlamydia control programmes.